Pleomorphic lobular carcinoma of the breast: molecular pathology and clinical impact. (March 2009) - Vargas, Ana-Cristina; Lakhani, Sunil R; Simpson, Peter T
Pleomorphic lobular carcinoma of the breast is a recently described morphological variant of classic invasive lobular carcinoma with an aggressive behavior. Morphologically, pleomorphic lobular carcinoma elicits a similar pattern of infiltrative growth as invasive lobular carcinoma, yet neoplastic cells have marked nuclear atypia and pleomorphism. Pleomorphic lobular carcinoma and the in situ counterpart, pleomorphic lobular carcinoma in situ, are frequently hormone receptor (estrogen-, progesterone- and androgen-receptor)-positive and E-cadherin and ββ-catenin-negative, attaining to their lobular nature. Tumors can also be positive for HER2, p53, ki67 and GCDFP-15 and harbor frequent chromosomal alterations involving gains on 1q and 16p, losses on 11q and 16q, and genomic amplifications in the region of 8q24, 11q13, 12q13, 17q12 and 20q13. Recent gene-expression profiling classified pleomorphic lobular carcinoma as ''molecular apocrine'' tumors reflecting the frequent apocrine differentiation of the tumors. In support for the aggressive biological features described for pleomorphic lobular carcinoma, accumulating clinical data demonstrate that it has an aggressive clinical course. It is now important to define the most appropriate management strategy for patients diagnosed with pleomorphic lobular carcinoma.